Characterization of differentially expressed genes in ovarian cancer by cDNA microarrays. Issue 1 (1st January 2005) - Zhang, X.; Feng, J.; Cheng, Y.; Yao, Y.; Ye, X.; Fu, T.; Cheng, H.
Abstract : The molecular events leading to the development and progression of ovarian carcinoma are not completely understood. We performed a large-scale survey for the identification of differentially expressed genes between ovarian carcinoma and normal ovarian tissue by using cDNA microarray analysis. We utilized 512 member human novel putative oncogene and tumor suppressor gene cDNA microarrays to study the differences in gene expression between ovarian carcinoma and normal ovarian tissues. Some differentially expressed genes have been further confirmed by immunohistochemical analysis. A total of 39 differentially expressed genes were identified, of which 16 and 23 were specifically expressed in ovarian cancer and normal ovarian tissue, respectively. The comparison of average signal of differentially expressed genes exhibited at least a twofold difference in expression. The differentially expressed genes may be related to the carcinogenesis and progression of the malignant growth. The use of cDNA microarrays allows simultaneous monitor of the expression of many genes, thereby it speeds up the identification of differentially expressed genes. It is essential for further exploration of the mechanisms of the disease.